Understanding John Dewey nature and cooperative intelligence - Campbell, James 1948- (Open Court, 1995)
Dewey is the most influential of American social thinkers, and his stock is now rising once more among professional philosophers. Yet there has heretofore been no adequate, readable survey of the full range of Dewey's thought. After an introduction situating Dewey in the context of American social and intellectual history, Professor Campbell devotes Part I to Dewey's general philosophical perspective as it considers humans and their natural home. Three aspects of human nature are most prominent in Dewey's thinking: humans as evolutionary emergents, as essentially social beings, and as problem solvers
Keywords: Dewey, John <1859-1952>; Dewey, John -- 1859-1952; Intelligentie; Menselijke natuur; Samenwerking; Philosophie; Einführung